Robert A. Askins and healthcare reform in interwar colonial Zimbabwe: The influence of British and trans-territorial colonial models (Historia, 2021)
Significant reforms of national healthcare systems took place across African colonies during the interwar period. These reforms were driven by changing notions of colonial governance, public health, and medical science and its various methods andimperatives of care. Although necessitated by local colonial concerns, connections between these schemes and other metropolitan and trans-imperial models are being uncovered, with an increasing number of historians underscoring complexinternational histories of interweaving models. This article plugs into this burgeoning research niche by unveiling a new case study, colonial Zimbabwe’s medical units scheme, a rural district healthcare initiative that was formulated in 1930 by Robert A.Askins, the colonial medical director and former medical officer of health in Bristol. This case study is used to demonstrate the ways in which local colonial healthcare policies evolved in contexts of entanglements and transfer of ideas within and acrosscolonies and empires. That said, individual colonial agents and their departments were responsible for pulling together all the disparate ideas and models into cohesive national colonial policies that simultaneously modernised and subjugated Africansociety.
Keywords: healthcare reform; colonial Zimbabwe; British Empire; imperial models; Askins; medical units